Ectodermal Dysplasia: A Review - Yasemin Yavuz; Mehmet Sinan Doğan; Myroslav Goncharuk-Khomyn (Makara Journal of Health Research, 2021)
Background: Ectodermal dysplasia is a complex group of genetic disorders identified through the abnormal development of ectodermal structures. It is a genetic disorder that affects the development or functions of tissues such as the teeth, hair, nails, and sweat glands.